Dynamical reconstruction of the global ocean state during the Last Glacial Maximum. (11th April 2017) - Kurahashi‐Nakamura, Takasumi; Paul, André; Losch, Martin
Abstract: The global ocean state for the modern age and for the Last Glacial Maximum (LGM) was dynamically reconstructed with a sophisticated data assimilation technique. A substantial amount of data including global seawater temperature, salinity (only for the modern estimate), and the isotopic composition of oxygen and carbon (only in the Atlantic for the LGM) were integrated into an ocean general circulation model with the help of the adjoint method, thereby the model was optimized to reconstruct plausible continuous fields of tracers, overturning circulation and water mass distribution. The adjoint‐based LGM state estimation of this study represents the state of the art in terms of the length of forward model runs, the number of observations assimilated, and the model domain. Compared to the modern state, the reconstructed continuous sea‐surface temperature field for the LGM shows a global‐mean cooling of 2.2 K, and the reconstructed LGM ocean has a more vigorous Atlantic meridional overturning circulation, shallower North Atlantic Deep Water (NADW) equivalent, stronger stratification, and more saline deep water. Key Points: LGM ocean reconstruction with an adjoint‐based data assimilation technique Physics‐based three‐dimensional interpolation/extrapolation of existing paleoceanographic data More stratified LGM ocean with a stronger but shallower AMOC